Cholesterol 25-hydroxylase acts as a host restriction factor on pseudorabies virus replication - Wang, Jiang; Zeng, Lei; Zhang, Li; Guo, Zhen-Zhen; Lu, Shao-Fang; Ming, Sheng-Li; Li, Guo-Li; Wan, Bo; Tian, Ke-Gong; Yang, Guo-Yu; Chu, Bei-Bei (Journal of general virology, 2017)
Cholesterol 25-hydroxylase (CH25H) catalyses the production of 25-hydroxycholesterol (25HC) from cholesterol by adding a second hydroxyl group at position 25. The aim of this study was to examine the antiviral effect of CH25H on pseudorabies virus (PRV), a swine pathogen that can cause devastating disease and economic losses worldwide. The results showed that porcine ch25h was induced by either interferon or PRV infection. PRV infection of porcine alveolar macrophages (3D4/21 cells) was attenuated by CH25H overexpression and enhanced by silencing of CH25H. Furthermore, treatment of 3D4/21 cells with 25HC inhibited the growth of PRV in vitro, suggesting that CH25H may restrict PRV replication by 25HC production. We further identified that the anti-PRV role of CH25H and 25HC was subject to their inhibitory effect on PRV attachment and entry. Collectively, these findings demonstrate that CH25H is an intrinsic host restriction factor in PRV infection of porcine alveolar macrophages.